A 6D CAD Model for the Automatic Assessment of Building Sustainability - Yung, Ping; Wang, Xiangyu (ARS, 2014)
Current building assessment methods limit themselves in their environmental impact by failing to consider the other two aspects of sustainability: the economic and the social. They tend to be complex and costly to run, and therefore are of limited value in comparing design options. This paper proposes and develops a model for the automatic assessment of a building’s sustainability life cycle with the building information modelling (BIM) approach and its enabling technologies. A 6D CAD model is developed which could be used as a design aid instead of as a post-construction evaluation tool. 6D CAD includes 3D design as well as a fourth dimension (schedule), a fifth dimension (cost) and a sixth dimension (sustainability). The model can automatically derive quantities (5D), calculate economic (5D and 6D), environmental and social impacts (6D), and evaluate the sustainability performance of alternative design options. The sustainability assessment covers the life cycle stages of a building, namely material production, construction, operation, maintenance, demolition and disposal.